The Initial Stages of Implementing the Western Quail Management Plan - Casey J. Cardinal; Rey A. Sanchez (National Quail Symposium Proceedings, 2017)
The Western Association of Fish and Wildlife Agencies (WAFWA) established the Western Quail Working Group (WQWG) in July 2009. A memorandum of understanding (MOU) was signed by the western agencies responsible for quail management (Arizona, California, Colorado, Idaho, Kansas, Montana, Nevada, Oklahoma, New Mexico, Oregon, Texas, Utah, and Washington) as ‘‘a cooperative agreement to improve management and implement strategies for conservation of western quail and their habitats.’’ The primary habitat management goals identified by the group are outlined in the Western Quail Management Plan, published by the Wildlife Management Institute in January 2010. Some of the past accomplishments of the WQWG, highlighted at recent WAFWA meetings, include shrub density reductions in New Mexico, riparian habitat restoration in Texas, private landowner habitat improvement cost-share in Kansas, and mesquite removal monitoring in Arizona. Management of western quail and their habitats has traditionally been accomplished on a relatively fine, local scale, so many of the current efforts to implement management practices identified in the plan are undocumented. A need identified by the WQWG is to better engage technical staff to guide outcomes and deliverables outlined in the plan. Additionally, the group is working to update the MOU to include Federal Land Management agencies, to better facilitate land management between state and federal agencies. A technical meeting with state and federal agency staff is scheduled for May 2017 in New Mexico to discuss state progress on implementing the Western Quail Management Plan, and how to increase state interest and efforts towards quail management. The discussions of the technical meeting will be presented at Quail 8.
Keywords: western quail; Western Quail Working Group; WQWG; Western Quail Management Plan; WAFWA